2007
DOI: 10.2337/db06-1269
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Spinally Mediated Hyperalgesia in Diabetes

Abstract: Hyperalgesia to noxious stimuli is accompanied by increased spinal cyclooxygenase (COX)-2 protein in diabetic rats. The present studies were initiated to establish causality between increased spinal COX-2 activity and hyperalgesia during diabetes and to assess the potential involvement of polyol pathway activity in the pathogenesis of spinally mediated hyperalgesia. Rats with 1, 2, or 4 weeks of streptozotocin-induced diabetes exhibited significantly increased levels of spinal COX-2 protein and activity, along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…The pathogenesis of pain in the setting of diabetes is complex. Previous studies have implicated involvement alterations in the peripheral kinin system (Gabra et al, 2006) and in peripheral vanilloid receptors (Hong and Wiley, 2005), in addition to described spinal and supraspinal mechanisms (Calcutt, 2002;Ramos et al, 2007) in the development of pain. The first study of sodium channels in peripheral nerve in PDN identified increases in RNA and protein of several voltage-gated sodium channel ␣ subunit isoforms, although in that study the investigators did not observe an increase in Na V 1.7 RNA or protein (Craner et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of pain in the setting of diabetes is complex. Previous studies have implicated involvement alterations in the peripheral kinin system (Gabra et al, 2006) and in peripheral vanilloid receptors (Hong and Wiley, 2005), in addition to described spinal and supraspinal mechanisms (Calcutt, 2002;Ramos et al, 2007) in the development of pain. The first study of sodium channels in peripheral nerve in PDN identified increases in RNA and protein of several voltage-gated sodium channel ␣ subunit isoforms, although in that study the investigators did not observe an increase in Na V 1.7 RNA or protein (Craner et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Formalin evokes an immediate short-lasting first phase due to the direct activation of TRPA1-expressing nociceptors (51) and a slower-onset, longer-lasting phase 2 that reflects a combination of ongoing sensory input and central sensitization in the spinal cord (37)(38)(39)(40). Several studies show that constitutive COX1 expression in the spinal cord is required for development of the second phase of the formalin test (36), while others point to a role for COX2 (26,49,50,52,53) or an involvement of both (48). Only a small, but significant, difference in the duration of formalin-mediated pain behavior in the second phase between nCOX2 -/-mice and their control littermates was observed, with no change in onset or peak of sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral tests. Hind-paw withdrawal responses to von Frey filaments (50% paw withdrawal threshold in gram of force applied) and radiant heat (latency to withdrawal in seconds) and also paw flinching following injection of 50 μl 0.5% formalin were measured in conscious unrestrained animals (82,83).…”
Section: Methodsmentioning
confidence: 99%